2017
DOI: 10.1097/iae.0000000000001335
|View full text |Cite
|
Sign up to set email alerts
|

High Myopia and Diabetic Retinopathy

Abstract: Using a contralateral eye study design prevented the influence of potential confounding factors inherent in similar previous case-control studies. On this basis, a protective role for high myopia against DR was established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 53 publications
0
9
0
2
Order By: Relevance
“…This produced a stronger peripheral retinal defocus and a more effective myopic control 18 , 25 , 26 , and hence, the magnitude of anisometropia was diminished sequentially. In Zhang and Chen’s study, the mean SE of the more myopic eyes was − 5.00 D (which fit the criteria of high myopia 27 ), whilst the average degree of anisometropia was 1.75 D and the inter-eye AL difference was 0.72 mm 18 . In contrast, the representative SE of the higher myopic eyes in our study was comparably milder (− 4.09 D).…”
Section: Discussionmentioning
confidence: 77%
“…This produced a stronger peripheral retinal defocus and a more effective myopic control 18 , 25 , 26 , and hence, the magnitude of anisometropia was diminished sequentially. In Zhang and Chen’s study, the mean SE of the more myopic eyes was − 5.00 D (which fit the criteria of high myopia 27 ), whilst the average degree of anisometropia was 1.75 D and the inter-eye AL difference was 0.72 mm 18 . In contrast, the representative SE of the higher myopic eyes in our study was comparably milder (− 4.09 D).…”
Section: Discussionmentioning
confidence: 77%
“…Since diabetics with high myopia have lower retinal VD in the superficial and deep macular retina than the diabetic patients without high myopia, what is the reason why the incidence of DR in the former is lower than that in the latter? Although the exact mechanism(s) underlying a protective anti-DR effect of long axial length is yet to be defined [2, 22, 23], several hypotheses have been suggested: (1) fundus changes in high myopia are often accompanied by thinning and atrophy of the choroidal and retinal tissue, greatly reducing retinal metabolism. Retinal atrophy and choroid thickness reduction may decrease oxygen requirements [24].…”
Section: Discussionmentioning
confidence: 99%
“…Diabetic retinopathy (DR) is a progressive microvascular disease of the retina, which is one of the most common and serious complications of diabetes, and a common cause of blindness in the middle age and elderly population [1]. In past clinical experience, we found that diabetics with high myopia had a lower incidence of DR than those without myopia [2][3][4]. A few clinical studies and epidemiological studies showed that high myopia could be a protective factor against DR.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, our findings may explain an interesting phenomenon. Epidemiological studies have shown that myopia, especially high myopia, is a protective factor for DR. 44 46 Retinal hypoxia has been established as a major factor contributing to the development of DR. 47 , 48 Studies have reported that the adjusted flow index of MCP and DCP decreased significantly, while the adjusted flow index of the SCP was unchanged or increased during the progression of DR, suggesting that the deep blood flow status is closely related to the occurrence and development of DR. 23 , 49 The VD of the DCPs is significantly increased in subjects with high myopia, and hypoxia is obvious in DR; therefore, patients with high myopia may have better adaptability to diabetic changes.…”
Section: Discussionmentioning
confidence: 99%